Negotiating the Complexities and Risks of Interdisciplinary Qualitative Research. Issue 1 (9th June 2017) - Trussell, Dawn E.; Paterson, Stephanie; Hebblethwaite, Shannon; Xing, Trisha M. K.; Evans, Meredith
This article interrogates the experiences of an interdisciplinary research team that engaged in a qualitative research program for over 5 years, beginning with the grant writing process through to knowledge dissemination. We highlight the challenges of constructing shared understanding and developing research synergies, embracing vulnerability and discomfort to advance knowledge, and negotiating risks of legitimacy and transcending disciplinary boundaries. Based on critical reflections from the research team, the findings call attention to the politics of knowledge production, the internal and external obstacles, and the open mindedness and emotional sensitivity necessary for interdisciplinary qualitative research. Emphasis is placed on relational and structural processes and mechanisms to negotiate these challenges and the potential for interdisciplinary research to enhance the significance of scholarly work.